Widening Access to Science-Oriented Programmes in Tertiary Institutions in Ghana Through Distance Education - Collins Kwabena Osei (Commonwealth of Learning, 2013)
An initiative in Science and Technology disciplines was introduced to expand access to KNUST programmes by distance. This study examined the level of access and challenges faced by learners in science oriented programmes offered by distance in KNUST. Analysis of data from 120 learners and 8 facilitators from three programmes indicated that the top-up programmes by distance increased enrolment and participation of learners. There were high rates of students’ persistence in the various programmes attributed to strong personal determination to succeed in achieving higher academic status, availability of learning materials for courses and support from family members. Lack of time as a result of work activities to delays in receiving course materials among students, and short contact hours to low remuneration for facilitators were challenges faced by respondents.